Influence of optimized lubrication-cooling and minimum quantity lubrication on the cutting forces, on the geometric quality of the surfaces and on the micro-structural integrity of hardened steel parts - Alves, Manoel Cléber Sampaio [UNESP]; Bianchi, Eduardo Carlos [UNESP]; Aguiar, Paulo Roberto de [UNESP]; Canarim, R. C. [UNESP] (FapUNIFESP (SciELO), 2012)
The is paper presents an analysis of the influence of minimum quantity lubrication (MQL), optimized and conventional cooling, using different cutting fluid volumes and flow rates, on the surface quality and integrity of hardened steel workpieces, in cylindrical plunge grinding with superabrasive CBN grinding wheels. The final quality of the workpieces were evaluated based on an assessment of output variables such as the behavior of: tangential cutting force, specific energy, surface roughness, roundness errors, acoustic emission, residual stresses, scanning electron microscopy (SEM) micrographs, and microhardness. The present analysis of the various forms of cutting fluid application identified cooling conditions which favor the minimization of cutting fluid usage, and shorter machining times without impairing the geometrical and dimensional parameters, surface finish and surface integrity of the workpieces. Among the various forms of cutting fluid application, optimized lubrication at higher outlet speeds showed the best performance, confirming the efficiency of the new nozzle concept employed in this study. The optimized and MQL processes were successful in maintaining the hardness and surface integrity of the ground workpieces. The only exception was the use of MQL with a flow rate of 40ml/h, which caused cracking and quenching of the workpiece surface. The lowest surface roughness values obtained with MQL were obtained using higher flow rates of lubricant. The surface roughness values obtained with MQL are high for the grinding process. Low-concentration CBN wheels, which are less expensive and subject to less wear, produce good results when associated with more efficient cutting fluid application techniques.
Keywords: CBN; Conventional lubrication; Grinding; Grinding wheel; Minimum quantity lubricant (MQL); Optimized lubrication